The effect of two different virtual reality videos on pain, fear, and anxiety during a venous blood sampling in children: A randomized controlled study - US, MAHMUT CANER (My University, 2023)
Aims: This study evaluated the effects of two different virtual reality (VR) methods on pain, fear, and anxiety during a venous blood sampling in children. Material and Method: This randomized controlled experimental study was conducted with 153 children aged 7-12 years and their parents who applied to the pediatric blood sampling unit of a training and research hospital. Research data were collected with the Wong-Baker Faces Pain Scale, Children’s Anxiety Meter-State scale, Children’s Fear Scale and Information Form. The two VR methods used were VR-Water skiing and VRWalking in nature. Results: The children’s mean pain scale score during the venous blood sampling was 1.29±1.11 with the VR-Water skiing; 1.28±1.16 with the VR-Walking in nature; and 4.34±1.41 (p<0.001) in the control group. The children’s mean anxiety scale score during the procedure was 0.82±1.01 with the VRWater skiing; 0.79±1.26 with the VR-Walking in nature; and 6.57±2.08 (p<0.001) in the control group. The children’s mean fear scale score during the procedure was 0.58±0.77 with the VR-Water skiing, 0.53±0.78 with the VR-Walking in nature; and 3.17±0.92 (p<0.001) in the control group. The children’s pain, anxiety and fear scale scores in the VR-Walking in nature and VR-Water skiing groups were similar (p>0.05). Conclusion: Two different VR videos were more effective than standard care in reducing pain, fear, and anxiety during a venous blood sampling. There was no significant difference in pain, anxiety and fear levels in the two different VR groups. Therefore, the use of VR goggles is recommended to reduce pain, anxiety, and fear during blood sampling in children aged 7-12 years old.

Amaç: Bu araştımanın amacı iki farklı sanal gerçeklik videosunun çocuklarda venöz kan alma işlemi sırasında oluşan ağrı, korku, anksiyete düzeyine olan etkisini değerlendirmektir. Gereç ve Yöntem: Bu randomize kontrollü deneysel araştırma bir eğitim ve araştırma hastanesinin çocuk kan alma birimine başvuru yapan 7-12 yaş arasındaki 153 çocuk ve ebeveynleri ile yürütüldü. Araştırma verileri Wong Baker Yüzler Ağrı Ölçeği, Çocuk Korku Ölçeği ve Çocuk Anksiyete Skalası-Durumluluk Ölçeği, Bilgi Formu ile toplandı. Bulgular: Araştırmada venöz kan örneği alma işlemi sırasında çocukların ağrı ölçeği puan ortalaması VR-Su kayağı grubunda 1.29±1.11, VR-Doğada yürüyüş 1.28±1.16, kontrol grubunda 4.34±1.41 idi. (p<0.001). İşlem sırasında çocukların korku ölçeği puan ortalaması VR-Su kayağı grubunda 0.58±0.77, VR-Doğada yürüyüş 0.53±0.78, kontrol grubunda 3.17±0.92 idi (p<0.001). İşlem sırasında çocukların anksiyete ölçeği puan ortalaması VRSu kayağı grubunda 0.82±1.01, VR-Doğada yürüyüş 0.79±1.26, kontrol grubunda 6.57±2.08 idi (p<0.001). VR-Su kayağı ve VRDoğada yürüyüş grubundaki çocukların ağrı, korku ve anksiyete ölçek toplam puan ortalamaları benzerdi (p>0.05). Sonuç: Çocuklarda sanal gerçeklik gözlüğü ile izletilen iki farklı videonun, venöz kan alma işlemi sırasında çocukların yaşadığı ağrı, anksiyete ve korku düzeyini azaltmada, standard bakıma göre daha etkili olduğu belirlendi. İki farklı sanal gerçeklik grubunda ise ağrı, anksiyete, korku düzeylerinde anlamlı bir fark olmadığı belirlendi. Bu doğrultuda, 7-12 yaş çocuklarda kan alma işlemi sırasında ağrı, anksiyete ve korkuyu azaltmak amacıyla sanal gerçeklik gözlüğünün kullanılması önerilmektedir.
Çocuklarda venöz kan alma işlemi sırasında kullanılan iki farklı sanal gerçeklik videosunun ağrı, korku ve anksiyete üzerine etkisi: Randomize kontrollü çalışma
Keywords: Virtual reality; pain; fear; anxiety; blood sampling; child; Sanal gerçeklik; ağrı; korku; anksiyete; kan alma; çocuk